Taking Back Islam - Jay Willoughby (International Institute of Islamic Thought, 2003)
This book is divided into nine sections: an opening section with intro ductory essays, followed by eight chapters that discuss the writers' views on certain issues. Each section contains several essays of anywhere from between three to six pages. Given the number of authors, I will mention only some of the points made in each section. In his introduction, Michael Wolfe lays out the book's general premise: Maybe it is time to stop looking to the "motherland" for our understandings of Islam and Islamic tradition. Maybe it is time to grow up. This call is sure to find a resonance among the many Muslims who are tired of imported imams and imported books that are so far removed from our own reality in the West. Farid Esack brings up an interesting point: Historically, Muslims have known only two paradigms: oppression (Makkah) and governing (Madinah). However, given current realities, they must adopt a third kind: peaceful coexistence in a state of equality, as done by those Muslims who emigrated to Abyssinia. In "Violence," Khaled Abou El Fadl notes that Islam is concerned with building and creating, and that ruining and destroying life is "an ultimate act of blasphemy against God." He writes that war is defensive and a last resort, that trade and technology are preferred, and that political discourses have displaced moral discourses. Aasma Khan discusses her small group (Muslims against Terrorism), which was set up in the days following 9/11 to educate people "about the incompatibility oflslam with terrorist activities, hatred, and violence." In "Democracy," Karen Armstrong reminds us of several important facts: modernity/democracy is a process; that in the Muslim world, modernity was imposed from above and has close ties with colonial subjugation/ dependence, instead of independence; and that is imitation and not inno vation. Religion, she asserts, can help people through the transition to modernity. Alex Kronemer states that "the greatest obstacle to democracy in the Muslim world is not 'Islam,' it is poverty, the lack of education, and corrupt and repressive regimes, many of which - and this is the important point - are supported by the democracies of the West." This raises the question of whether the West really wants democracy in the Muslim world ...